Improving English Speaking Skill By Structured Dialogue through Problem Based Learning (PBL) - Imam Mudofir; Alief Sutantohadi; Halim Ahmad Faizin; Muhyiddin Aziz; Eda Maaliah; Yulius Harry Widodo; Moh. Farid Maftuh (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
In this study, which began with an initial speaking score of 60.5, the main objective was to enhance students’ English-speaking skills through structured dialogue by applying Problem-Based Learning (PBL). The research was conducted using a Collaborative Classroom Action Research approach, which followed four key stages: planning, action, observation, and reflection. These stages were carried out in distinct cycles, with each cycle consisting of two meetings. Data were collected through several instruments, including structured dialogue tasks to measure speaking performance, questionnaires to evaluate students’ perceptions of PBL practice, and field notes to capture classroom dynamics. The participants of this study were fourth-semester students of the D3 English Study Program at the State Polytechnic. The findings indicated a significant improvement in students’ English-speaking performance across the two cycles. In Cycle I, the total score achieved was 1,500, with an average of 75 and a success percentage of 70%. In Cycle II, the total score increased to 1,700, with an average of 85 and a success percentage of 90%. This shows a substantial enhancement not only in terms of numerical achievement but also in students’ active engagement and confidence during structured dialogue activities. Furthermore, the effectiveness of the PBL approach in facilitating learning also improved notably. In Cycle I, the average effectiveness score was 6.4, while in Cycle II, it rose to 9.4. These findings suggest that integrating structured dialogue with PBL provides an effective strategy to foster students’ speaking proficiency. It also highlights the potential of collaborative classroom action research in promoting reflective teaching practices and sustained learning improvement.